If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 28 = 6x + 12 Reorder the terms: 28 + 10x = 6x + 12 Reorder the terms: 28 + 10x = 12 + 6x Solving 28 + 10x = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 28 + 10x + -6x = 12 + 6x + -6x Combine like terms: 10x + -6x = 4x 28 + 4x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 28 + 4x = 12 + 0 28 + 4x = 12 Add '-28' to each side of the equation. 28 + -28 + 4x = 12 + -28 Combine like terms: 28 + -28 = 0 0 + 4x = 12 + -28 4x = 12 + -28 Combine like terms: 12 + -28 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 10x-7=40x+17 | | 11(3+y)=5(2y+8) | | 3x^2+12x+48=0 | | x^2=2(4-x) | | 24=4(x+4) | | 9x-4y=-37 | | x^2+4(x-3)=0 | | 3(x^2+2x)=9 | | 3x+(x-2)+(2x-1)=18 | | 1-5x+6x^2=0 | | 5-3x-2x^2=0 | | -5y+6=-4(2y+3) | | x+3=2x^2 | | y=8-12+2y | | 5x+20x=1320 | | 5x-20x=1320 | | -(a-5)+7=-(8+3a) | | -4(1+2n)=-2(n-1) | | 90=10(x+16) | | x+(x-2)= | | 17x=-12 | | 5(v-7)=-39+3v | | 6(x+1)=-5x-5 | | 35=10b+50 | | 2x+4(2x+7)=3(2x+4) | | -(3+2x)=17 | | 4b^2=9 | | 6-(-6b-3)=-3b-27 | | -32-5x=2(4x-6)-7 | | a-0.66667a=8 | | -3(2z-5)=-2z-3z+21 | | 6-x=8-2x |